2019
DOI: 10.1111/are.13992
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fasting on metabolic and immunological responses of common carp ( Cyprinus carpio ) to a further acute stress

Abstract: Common carp were fasted for 0, 3 and 14 days prior to exposure to a 2‐hr crowding stress. Serum cortisol, glucose, lactate, T4, T3, serum alternative complement (ACH50), lysozyme, total immunoglobulin (Ig) and blood WBC were determined before and 0, 6 and 24 hr after the crowding stress. Three days of fasting led to a significant decrease in serum levels of lactate and thyroid hormones. Fourteen days of fasting led to initiation of physiological process to maintain serum glucose by increase in serum cortisol l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…The elevated serum proteins and ACH50 activity may be associated with the health of the liver (the site for many protein syntheses), and dietary licorice was reported to be hepatoprotective in fish (Elabd et al., 2016, 2017; Yin et al., 2011). Also, the immunostimulant mechanisms of licorice may be attributed to the presence of immunoregulative compounds such as glycyrrhizin, glycyrrhetinic acid, licochalcone A, glycyrrhizic acid, polysaccharides and saponins (Nassiri Asl & Hosseinzadeh, 2008) and increased fish welfare and health by dietary licorice supplementation (see below), as it has been shown that stress conditions impact fish health and induce immunosuppression in fish (Hoseini et al., 2019; Naderi et al., 2019; Tort, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The elevated serum proteins and ACH50 activity may be associated with the health of the liver (the site for many protein syntheses), and dietary licorice was reported to be hepatoprotective in fish (Elabd et al., 2016, 2017; Yin et al., 2011). Also, the immunostimulant mechanisms of licorice may be attributed to the presence of immunoregulative compounds such as glycyrrhizin, glycyrrhetinic acid, licochalcone A, glycyrrhizic acid, polysaccharides and saponins (Nassiri Asl & Hosseinzadeh, 2008) and increased fish welfare and health by dietary licorice supplementation (see below), as it has been shown that stress conditions impact fish health and induce immunosuppression in fish (Hoseini et al., 2019; Naderi et al., 2019; Tort, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the extract of licorice could improve the resistance of fish to stress and infection (Wang et al., 2007). Improved antioxidant activities and suppressed cortisol levels can explain enhanced immune functions in juvenile common carp fed 20 and 30 g/kg dietary licorice, as there are strong relationships between immune function and antioxidant defence (Naderi et al., 2019) as well as stress level (Hoseini et al., 2019; Tort, 2011; Yousefi et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in aquaculture, fasting carp for 14 days makes them more susceptible to crowding stress, although short fasting times (i.e. 3 days) have significant effects on fish health (Hoseini, Abtahi, & Yousefi, ). However, little is known about the combined effects of fasting and prolonged catch duration on the welfare or product quality of farmed fish.…”
Section: Introductionmentioning
confidence: 99%
“…Crowding depletes tissue energy stores, increases lactate and causes osmoregulatory imbalance in fish (Cooke & Suski, 2005) and increases cortisol and haematocrit levels (Merkin, Roth, Gjerstad, Dahl-Paulsen, & Nortvedt, 2010). 3 days) have significant effects on fish health (Hoseini, Abtahi, & Yousefi, 2019). Similarly, in aquaculture, fasting carp for 14 days makes them more susceptible to crowding stress, although short fasting times (i.e.…”
mentioning
confidence: 99%